Analisis Pajak Penghasilan Badan Pada Perusahaan Manufaktur Sub Sektor Otomotif dan Komponen - Irma Herliza Rizki; Oky syahputra (Jurnal Manajemen Bisnis Eka Prasetya, 2023)
This study aims to determine whether profitability has a significant effect on corporate income tax, to find out whether operational costs have a significant effect on corporate income tax and to find out whether profitability and operational costs have a significant effect on corporate income tax on automotive companies and components listed on the Indonesia Stock Exchange in the 2014 -2018 period The population in this study were all automotive companies and components listed on the Indonesia Stock Exchange which numbered 15 companies. By using purposive sampling, we obtained a total sample of 11 companies. The results of the research analysis show that profitability and operational cost has an influence on corporate income tax on automotive companies and components listed on the Indonesia Stock Exchange in the 2014-2018 period. F test shows that profitability and operational cost has an influence on corporate income tax on automotive companies and components listed on the Indonesia Stock Exchange in the 2014-2018 period. The result of determination coefficient (R Square) shows that corporate income tax can be explained by profitability and operational cost. As of the remaining can be explained by other variable which is not included on this research such as liquidity, leverage and earnings per share.